2017
DOI: 10.1038/nplants.2017.56
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoscale movements of cellulose microfibrils in primary cell walls

Abstract: The growing plant cell wall is commonly considered a fiber-reinforced structure whose strength, extensibility and anisotropy depend on the orientation of crystalline cellulose microfibrils, their bonding to the polysaccharide matrix, and matrix viscoelasticity1–4. Structural reinforcement of the wall by stiff cellulose microfibrils is central to contemporary models of plant growth, mechanics, and meristem dynamics4–12. Although passive microfibril reorientation during wall extension has been inferred from theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
128
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(140 citation statements)
references
References 36 publications
12
128
0
Order By: Relevance
“…This idea springs from the high stiffness of cellulose microfibrils but fails to consider how cellulose microfibrils are connected to one another to form a mechanically strong material. A recent study that combined extensometry with atomic force microscopy and different forms of cell wall strain showed that both cellulose microfibrils and matrix polymers, predominantly pectins, bear the tensile load of elastically stretched onion walls (Zhang et al, 2017). This confirms the mechanical significance of the matrix at the molecular scale and adds impetus to recent interest in the state of pectins in growing cell walls and the need for better models of cell wall mechanics (Peaucelle et al, 2012;Xiao et al, 2014;Levesque-Tremblay et al, 2015).…”
Section: Discussionmentioning
confidence: 77%
“…This idea springs from the high stiffness of cellulose microfibrils but fails to consider how cellulose microfibrils are connected to one another to form a mechanically strong material. A recent study that combined extensometry with atomic force microscopy and different forms of cell wall strain showed that both cellulose microfibrils and matrix polymers, predominantly pectins, bear the tensile load of elastically stretched onion walls (Zhang et al, 2017). This confirms the mechanical significance of the matrix at the molecular scale and adds impetus to recent interest in the state of pectins in growing cell walls and the need for better models of cell wall mechanics (Peaucelle et al, 2012;Xiao et al, 2014;Levesque-Tremblay et al, 2015).…”
Section: Discussionmentioning
confidence: 77%
“…These inferences about microfibril movements gain support from a recent study in which the nanoscale movements of cellulose microfibrils were directly monitored by AFM (Zhang et al, 2017). The cell wall was extended in a well-defined series of extensions that included elastic and plastic strains imposed by axial force as well as time-dependent creep induced by treatment with an endoglucanase with wallloosening activity.…”
Section: Insights From Afm Of Epidermal Cell Wallsmentioning
confidence: 84%
“…These purely mechanical responses of walls differ in an essential way from the sustained wall expansion that occurs during cell growth (Cosgrove, 2016b;Zhang et al, 2017), which depends on continuous loosening by expansins or other wall-loosening agents (Cosgrove, 2016a). Wall loosening results in wall stress relaxation that drives cell growth.…”
Section: Wall Stress Relaxation Drives Cell Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…AM-AFM has been successful in characterizing biomass (Kirby et al, 1996;Salvadori et al, 2014;Farahi et al, 2017) and in particular the architecture of plant cell walls at the molecular level which in turn is essential in improving lignocellulosic feedstock properties (Zhang et al, 2013b(Zhang et al, , 2017Keplinger et al, 2014;Torode et al, 2018). AM-AFM mapping of cellulose topography revealed the right-handed twisted nature of microfibrils and the periodic distribution of glucose and fiber unit along the microfibrils (Hanley et al, 1997).…”
Section: Amplitude Modulation Afm (Am-afm): Structural Propertiesmentioning
confidence: 99%